The Image Problem of Child Psychology in French Children's Prose (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article is about the image problem of child psychology in french children's prose. Children's literature is a variable phenomenon that is directly related to the age of the reader, the historical period and the social environment in which the age of the reader is taken into account.  Another characteristic of children's literature is its richness of action. It depends on the demand for the plot in children's literature.